Compound composite odontoma with unusual number of denticles – A rare entity - Urvashi Sharma; Rahul Sharma; Anubha Gulati; Renu Yadav; Krishan Gauba (Saudi Dental Journal)
Compound odontoma is stated to be a hamartomatous lesion rather than a true odontogenic tumour. It has an unknown etiology and often suspected when there are retained deciduous teeth in children. Early detection and surgical enucleation of the tumour is recommended to prevent impaction of unerupted teeth. In this index case, multiple denticles or rudimentary teeth, numbering 37 were enucleated from the maxillary anterior region of a 17-year old male, which makes this case unusual. Evidence of concrescence, fusion and dilaceration were observed in the denticles enucleated, the size of which varied from 4 mm to 12.5 mm. Keywords: Odontoma, Compound odontoma, Odontogenic tumours, Denticles